2010
DOI: 10.1039/b9nr00233b
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the conductivity of peptide nanotube networks prepared by enzyme-triggered self-assembly

Abstract: We demonstrate that nanotubular networks formed by enzyme-triggered self-assembly of Fmoc-L3 (9-fluorenylmethoxycarbonyl-tri-leucine) show significant charge transport. FT-IR, fluorescence spectroscopy and wide angle X-ray scattering (WAXS) data confirm formation of beta-sheets that are locked together viapi-stacking interactions. Molecular dynamics simulations confirmed the pi-pi stacking distance between fluorenyl groups to be 3.6-3.8 A. Impedance spectroscopy demonstrated that the nanotubular xerogel networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 34 publications
(46 reference statements)
9
130
0
1
Order By: Relevance
“…13 Another peak at d = 3.76 Å signifies the π−π interaction between the phenyl rings of the molecules in the three-dimensional network structure ( Figure 3). 56 Combining these results obtained from X-ray diffraction and FT-IR analyses, it can be concluded that the gelator peptide molecules are self-assembled in the gel state to form a β-sheet-like structure. A probable mechanistic model is shown in Figure S8.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…13 Another peak at d = 3.76 Å signifies the π−π interaction between the phenyl rings of the molecules in the three-dimensional network structure ( Figure 3). 56 Combining these results obtained from X-ray diffraction and FT-IR analyses, it can be concluded that the gelator peptide molecules are self-assembled in the gel state to form a β-sheet-like structure. A probable mechanistic model is shown in Figure S8.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…2), it is apparent that the bundled chiral supramolecular structures represent a highly ordered state of these systems that is preferentially obtained at higher catalyst concentrations. It is worth noting that the formation of well-aligned extended one-dimensional p-stacked nanofibres is of relevance to supramolecular electronics [30][31][32][33] . The results shown here imply that supramolecular electro-conductivity may be induced and controlled by catalytic self-assembly.…”
mentioning
confidence: 99%
“…It has been demonstrated that p-conjugated organic components (e.g., oligothiophene, [8,9] naphthalene, [10] and perylene) [11,12] linked to oligopeptides can form 1D structures, but the p-electron-functionalized groups were typically embedded within the oligopeptide motifs (i.e., nonconductive components), making it difficult to fabricate nanoelectronic devices and characterize the conductivity directly. [8][9][10][11][12][13][14] Herein we demonstrate how terminally functionalized p-conjugated peptides assemble into 1D nanostructures to give strong p-p intermolecular electronic communication, which is confirmed by direct-conductivity measurements for the first time.…”
mentioning
confidence: 59%